Fiscal management practices and school performance of Tesda Technology Institutions (TTIS) in Panay Island - Jonna Jay Gervero; Evangeline Ybañez (President University, 2022)
Finance is the backbone of the educational system which challenges administrators’ leadership and capabilities, especially educational programs and projects involving greater responsibilities and liabilities. The study determined the level of fiscal management practices of TESDA Technology Institutions (TTIs) in financial literacy, financial planning, and transparency and degree of school performance and their relationship with faculty and staff. Descriptive-correlational and mixed methods were used with quantitative and qualitative data. A survey questionnaire and in-depth interview were used in data gathering. The respondents were two hundred eleven (211) faculty and staff of TESDA Technology Institutions in Panay Island. Frequency count, percentage and mean were used while t-test for independent samples, and Pearson r for relationship. Results on the level of fiscal management practices when taken as a whole and in terms of financial literacy, financial planning, and transparency was found “satisfactory”, with financial literacy having the highest mean. The degree of school performance in terms of quality service and student service efficiency was also “satisfactory”, with quality service having the highest mean. Significant differences existed when respondents were grouped according to sex and educational attainment. However, no significant differences occurred between the level of fiscal management practices and variables such as position, age, civil status, and length of service. No significant differences were found on the degree of school performance of TESDA Technology Institutions in terms of quality service and students service efficiency as to sex, position, age, civil status, and length of service, except on educational attainment. Significant relationships were found on the level of fiscal management practices and the degree of school performance of TESDA Technology Institutions.